Predictors for surgical referral in patients with pancreatic cystic lesions undergoing endoscopic ultrasound - Azar, Riad R. (2016)
Objective: Endoscopic ultrasound (EUS) plays an integral role in the evaluation of pancreatic cysts lesions (PCLs). The aim of the study was to determine predictors of surgical referral in patients with PCLs undergoing EUS. Methods: We performed a multicenter retrospective study of patients undergoing EUS for evaluation of PCLs. Demographics, EUS characteristics, and fine-needle aspiration results were recorded. Patients were categorized into surgery or surveillance groups on the basis of post-EUS recommendations. Univariate and multivariate analyses were performed to identify predictors of surgical referral. Results: 1804 patients were included. 1301 patients were recommended to undergo surveillance and 503 patients were referred for surgical evaluation, of which 360 patients underwent surgery. Multivariate analysis revealed the following 5 independent predictors of surgical referral: symptoms of weight loss on presentation (odds ratio [OR], 2.69; 95% confidence interval [CI], 1.44–5.03), EUS findings of associated solid mass (OR, 7.34; 95% CI, 3.81–14.16), main duct communication (OR, 4.13; 95% CI, 1.71–9.98), multilocular macrocystic morphology (OR, 2.79; 95% CI, 1.78–4.38), and fine-needle aspiration findings of mucin on cytology (OR, 3.06; 95% CI, 1.94–4.82). Conclusions: This study identifies factors associated with surgical referral in patients with PCLs undergoing EUS. Future studies should focus on creation of risk stratification models to determine the need for surgery or enrollment in surveillance programs.